UNRAVELING THE MANIFESTATION OF VITAMIN D-DEPENDENT RICKETS TYPE 1 IN PREMATURE INFANT - Salihhuddin, Shahidatul Munirah Mohammad; Hussain, Suhaimi (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Vitamin D-dependent rickets type 1 (VDDR1) is one of the genetic causes of calciopenic rickets. This rare autosomal recessive disorder is due to the defective 1-α hydroxylase which results in deficient active vitamin D or 1,25-dihydroxyvitamin D. It manifests as stunted growth, skeletal deformities and bone pain in young children. Diagnosing this uncommon disease requires a high index of clinical suspicion and is confirmed through genetic testing. CASE A seven-month-old female was born prematurely at 24 weeks of gestation with birth weight of 600 grams. Both parents were non-consanguineous. She had a stormy neonatal period with prolonged ventilation due to severe respiratory distress syndrome. In early neonatal phase, she had hypocalcaemia and hypophosphataemia, with subsequent gradual increment of alkaline phosphatase (ALP) – the overall picture initially pointing towards osteopaenia of prematurity. With time, she developed severe skeletal deformities which were bowing of the limbs, palpable widening of distal radius and double malleoli, Harrison’s groove and long bones fracture. Apart from low calcium (1.88 mmol/L) and phosphate (1.32 mmol/L), other bone profiles showed: 25-hydroxyvitamin D levels were insufficient (47 nmol/L), both parathyroid hormone (PTH, 47.9 pmol/L) and serial ALP (1008 U/L) were elevated. A 1,25-dihydroxyvitamin D level was not investigated in view of financial limitations. Radiological imaging revealed rickets changes over the metaphyseal plate, including Looser’s zone at the humerus and tibia. Considering the severe clinical manifestations of rickets, but inconsistent with insufficient level of stored 25-hydroxyvitamin D, this indicates deficient active vitamin D level that is consistent with clinical VDDR1. The whole exome sequencing was negative, but further workup for more expensive genetic study such as whole genome sequencing will incur additional costs. CONCLUSION Osteopaenia of prematurity with nutritional deficiency is commonly observed in preterm infant. Nonetheless, the presence of severe rickets with inconsistent bone profile warrants further work-up for other alternative diagnoses, including VDDR1.